Enhancing Students’ Local Knowledge Through Themed Garden Project - Esa, Norizan (EDP Sciences, 2015)
Traditional or local knowledge is a major issue to be focused on, particularly since the implementation of the Strategic Plan for Biodiversity 2011–2020 and the Aichi Targets “Living in Harmony with Nature”. According to the strategic goals, by 2020, conservation of biodiversity and its sustainable use incorporate what local and indigenous communities have within their traditional knowledge, innovation and practice and their customary use of biological resources are respected at all relevant levels. The older generation among the local people usually use medicinal herbs for various ailments, health care and other cultural purposes. However, encroaching industrialization and the changes in today’s life styles are responsible for the decreasing practice in the local use of herbs especially for healing purposes. It is, therefore, felt worthwhile to encourage young generations such as school children to gain knowledge about these local herbs and record the native uses of these herbs before the information is lost. One biodiversity education program was conducted to facilitate secondary school students to set up a themed garden and find out the local knowledge of the plants they grew in their garden from their family members or communities. The findings revealed that students’ local knowledge on healing improved after they joined the program. Therefore, it is proposed that the themed garden project can enhance students’ local knowledge.